Exploring E-books evaluation: issues, evaluation criteria and techniques - Zakaria, Noor Azura; Ahmad Mizanudin, Putra Ahmad Maarifudin; Mohammed, Siti Asma; Azuddin, Muna; Rosman, Romzie (Global Academic Excellence, 2025)
E-book evaluation involves balancing technical and user-centered criteria to ensure usability and functionality across various contexts and platforms. This study reviews existing literature to examine the issues, challenges, evaluation criteria, and techniques used in e-book evaluation. Identified challenges include the lack of standardization in interfaces and functionalities, licensing restrictions such as Digital Rights Management (DRM), variability in accessibility features across formats, and the complexity of criteria influenced by context and user needs. Commonly used evaluation criteria include readability, accessibility, interactivity, efficiency, and navigation. The evaluation approaches vary across domains, with educational settings focusing on engagement and knowledge retention, academic contexts prioritizing accuracy and depth, and professional environments emphasizing practicality and efficiency. Methodologies such as mixed methods, usability testing, and surveys are used to measure user satisfaction and technical performance. This review offers valuable insights for developers, educators, and researchers. Additionally, guiding better user experiences in future e-book design and innovation